In situ bioremediation and natural attenuation of dinitrotoluenes and trinitrotoluene - Han, Sungsoo (Georgia Institute of Technology, 2008)
Contamination of soils and groundwater with nitroaromatic compounds such as 2,4,6-trinitrotoluene (TNT) and dinitrotoluenes (DNTs) has drawn considerable attention due to widely distributed contamination sites and substantial efforts for cleanup. Two isomers of DNT, specifically 2,6-dinitrotoluene (2,6-DNT) and 2,4-dinitrotoluene (2,4-DNT), occur as soil and groundwater contaminants at former TNT production sites. The discovery of bacteria that use DNT isomers as electron donors has encouraged bioremediation at contaminated sites. Current work is extending the existing engineered bioremediation to naturally occurring in situ biodegradation and focuses on the application of natural attenuation (NA) as a remediation strategy for residual DNT at contaminated sites. More specifically this research evaluated factors influencing in situ bioremediation of DNTs and TNT in surface soils, vadose zones, and saturated medium. Applications involving surface soils and vadose zones investigated the potential of water infiltration to promote in situ bioremediation. Studies in saturated media were more applicable to NA. Factors that were also considered in studies conduced included: 1) the presence and distribution of degrading microbes in field soils (Barksdale, WI); 2) the dissolution and bioavailability of contaminants in historically contaminated soils; and 3) the effect of mixtures of contaminants (i.e., DNTs and TNT) on biodegradation processes. This research provided information useful for practitioners considering an in situ bioremediation NA as a remedial solution for contaminated sites. Under the condition simulating downflow of surface waters or rainwater, the rapid rate of DNT degradation could be facilitated by the availability of oxygen in the soil gas without concern of toxicity (i.e., nitrite evolution and pH drop) and addition of nutrients. As a result, in situ bioremediation or NA should be strongly considered as a remedial option for Barksdale soils and similar sites where relatively low concentrations of DNT isomers are present as contaminants. At TNT contaminated sites TNT was not mineralized by indigenous microorganisms despite oxidative biotransformation, and mixed culture capable of growth on DNT also could not develop the mineralization of TNT during DNT degradation. This suggests that the mixtures of contamination did not improve the potential for in situ TNT bioremediation.